Os desafios da linguagem docente no trabalho com alunos inclusos durante a pandemia - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The experience with teaching with included students has always given rise to many thoughts among teachers in general, through the challenges we encounter in everyday life. The pandemic contributed to the possible increase in obstacles, thus generating doubts regarding incentives within the school environment, whether in infrastructure or even better professional courses for teachers. The following survey, carried out with Elementary School II teachers, helps with these assertive or unfavorable questions arising from the pandemic moment we are experiencing. In this sense, we try to understand, within the learning process, the challenges encountered by two teachers who assisted two students included during the pandemic period, as well as understanding their greatest diversities in this remote teaching, listing positive and negative points of the use of technology in training of students, especially considering students with disabilities. The methodology used in the research took place in three moments: (1) bibliographic review, (2) interview with professors and (3) analysis of the collected data. During the course of the investigation, the importance of the support network made up of family and school became evident, in order to ensure the well-being of the student and his development in the teaching-learning process.
Keywords: Pandemia; Educação; Desafios Docente; Pandemic; Education; Teaching Challenges; CNPQ::LINGUISTICA, LETRAS E ARTES